The Effect of Word of Mouth in Integrated Marketing Communication (IMC) on Decision to Buy through Intention to Buy in Citraland City Losari - Winardi, Anastasia Amelia (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to determine the effect of personal selling, sales promotion, events and word of mouth on decision to buy through intention to buy with a case study at CitraLand City Losari. This research was conducted using quantitative methods with PLS (Partial Least Square) analysis. Data collection was carried out by means of a questionnaire to 85 buyer respondents at CitraLand City Losari in 2022 with repeated purchases excluded. From the results of this study, it was found that personal selling and sales promotion had no effect on intention to buy. Events and word of mouth have an effect on intention to buy, word of mouth has a positive and significant effect on decisions to buy. Then intention to buy has a significant effect on decisions to buy. These findings provide insights regarding marketing communication strategies and improvements to these strategies to improve purchasing decisions on products at CitraLand City Losari.